Capacitated Stochastic Fractional Transhipment Problem - Javaid, Shakeel; Gupta, S. N (Journal of Commerce and Trade, 2008)
The present paper analyses a transshipment type fractional programming under stochastic demand. The objective is to maximize the expected profitability of the total transshipment schedule, the net expected profitability being defined as the total expected revenue minus the loss in transshipment. The stochastic transshipment problem is reduced to an equivalent deterministic transportation problem for which an algorithm is developed and numerically illustrated.